Traffic Scheduling For QOS Provisioning In Broadband Wireless Access Networks - Yin, Tang Sze (2010)
This thesis presents a methodology for extending the existing wireless scheduling algorithms to cope with the heterogeneous traffic environment, particularly in the uplink direction. More specifically, the Weighted Round Robin (WRR) scheduling and the combination of the Modified Largest Weighted Delay First and Proportional Fair (M-LWDF-PF) scheduling are considered, and their effectiveness in providing QoS differentiation for multiple traffic types is investigated.